Penentuan Prioritas Pemeliharaan Daerah Irigasi Akibat Refocussing Anggaran Menggunakan AHP (Studi Kasus Wilayah UPTD III Kabupaten Deli Serdang) (Syntax Corporation Indonesia, 2023)
Limited funds due to budget refocusing are often an obstacle inrioritisation for irrigation maintenance, including in Deli Serdang Regency. In prioritizing irrigation maintenance, it is necessary to analyze the dominant criteria and priority order of irrigation maintenance areas, which is currently being sought only in deliberations and consultations from the community. This study aims to analyze the dominant criteria that need to be considered in making irrigation area maintenance priorities and to analyze the priority order of irrigation area maintenance in the Technical Implementation Unit (UPT) Region III which is included in the activity plan in Deli Serdang Regency. This research is a quantitative method through a questionnaire with a sampling technique using purposive sampling based on stakeholders who understand he feature criteria at the location of the intended irrigation area and data analysis techniques using the Analytical Hierarchy Process (AHP). The results of the research indicate that the dominant criterion that needs to be considered is the budget target criterion with a value of 0.33. The order of priority for maintenance of irrigation areas is DI Jati Baru as priority 1 with a weight of 0.14, priorities 2 and 3 are DI Pertumbuk and DI Sei Tuan with a weight of 0.13, priority 4 is DI Johar Baru with a weight of 0.12, priority 5 is D.I Kotasan with a weight of 0.11, priorities 6 and 7 are D.I Jaharum B and D.I Tj. Garbus Kampung with a weight of 0.10, priority 8 is D.I Tanjung Siporkis with a weight of 0.09, and priority 9 is D.I Kampung Melayu with a weight of 0.07.